Proceedings of the 16th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Innovation in Educat 2018
DOI: 10.18687/laccei2018.1.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy neural System Model for Online Learning Styles Identification, as an Adaptive Hybrid ELearning System Architecture Component

Abstract: In the present work, we present a Fuzzy Neural System Model for online identification of Learning Styles which gives support for contents personalization. The model was developed to serve as a component for an Adaptive Hybrid E-Learning System Architecture, which focus on a high degree of customization and content adaptation. We proposal a Hybrid System model, in which techniques of Neural Networks, Fuzzy Logic and Case Based Reasoning are incorporated into the multiagent system. Finally, the authors present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The architecture of the proposed mulit-agent model, as with the description of its components, can be found in Alfaro et al [11], which is shown in Figure 1. Fig.…”
Section: B Proposal For E-learning Adaptive System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The architecture of the proposed mulit-agent model, as with the description of its components, can be found in Alfaro et al [11], which is shown in Figure 1. Fig.…”
Section: B Proposal For E-learning Adaptive System Architecturementioning
confidence: 99%
“…1. Architecture of the multi-agent system [11] The implementation of the proposed intelligent agents was realized utilizing the JADE platform, which is an agent platform distributed with a container for each host, in which the agents are executed and which possesses storage for diverse languages and ontologies, complying with FIPA (Foundation for Intelligent Physical Agents) specifications, for which developed agents can easily be integrated in other languages and platforms, including owners.…”
Section: B Proposal For E-learning Adaptive System Architecturementioning
confidence: 99%
“…Resource categories and their relation to LS. Source:Alfaro, Rivera, Luna-Urquizo, Castañeda, & Fialho (2018) …”
mentioning
confidence: 99%